Răspunsuri

2014-06-05T17:23:22+03:00
                            
I2x - 6I  =  2x + 6 daca 2x - 6 ≥ 0  ⇒  I2x - 6I = 2x - 6 daca  x ≥ 3
I2x - 6I = -(2x - 6) = 6 - 2x daca x < 3

Ix - 3I = x - 3 daca x - 3 ≥ 0  ⇒  Ix - 3I  = x - 3 daca x ≥ 3
Ix - 3I = -(x - 3) daca x < 3

Descompunem ecuatia in 2 ecuatii:

Pentru x ≥ 3   
⇒   (2x - 6) + (x - 3) = 15 
2x + x - 6 - 3 = 15
3x = 15 + 9
3x = 24
x₁ = 24 / 3 = 8

Pentru x < 3
(6 - 2x) + (3 - x) = 15
6 + 3 - 2x - x = 15
-3x = 15 - 9
-3x = 6
x₂ = -6/3 = -2